Social Well-being Research Problems in Modern World; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Surtaeva N. N. Nadezhda; Krivykh S. V. Sergei; Buvakov K. V. Konstantin Vladimirovich; Kazakova O. A. Oksana Aleksandrovna; Soboleva A. V. Anastasia (2017, 2017)
Title screen